Optimizing ultramicroporous hard carbon spheres in carbonate ester‐based electrolytes for enhanced sodium storage in half‐/full‐cell sodium‐ion batteries. Issue 3 (22nd June 2022) - Nagmani; Kumar, Ananya; Puravankara, Sreeraj
Abstract: Sodium‐ion batteries (SIBs) have received considerable attention as promising next‐generation energy storage systems due to a large abundance of sodium and ion storage chemistry similar to that of lithium‐ion batteries (LIBs). We report ultramicroporous hard carbon microspheres (HCMSs) derived from sucrose via a microwave‐assisted solvothermal reaction as anode for SIBs. Because of the HCMSs with a larger interlayer spacing in graphitic domains and ultramicropores, it delivers excellent 3‐RC features (reversible capacity, rate capability, and retention of capacity) reported to date for hard carbons derived from sugar‐based carbon precursors through electrolyte optimization of carbonate esters (EC:PC, EC:DEC, EC:DMC). The HCMS‐PC delivered the best reversible capacity of 265 mAh g −1 at a current density of 300 mA g −1, showing 85.8% capacity retention after 100 cycles and 66.3% capacity retention after 500 cycles in a half‐cell. A full‐cell fabricated with an HCMS‐PC anode and a Na3 V2 (PO4 )3 cathode delivered reversible capacities of 81 and 48 mAh g −1 at current densities of 30 and 300 mA g −1, respectively. Abstract : Among the carbonate‐based electrolytes, 1 M NaClO4 in EC:PC delivered excellent capacity at a higher C‐rate and stable solid electrolyte interface and higher Coulombic efficiency. The sucrose‐based microsphere hard carbon showed the maximum discharge capacity of 265 mAh g −1 at a 1 C rate, with good capacity retention of 85.8% after 100 cycles and 66.3% after 500 cycles in the optimized electrolyte.